THE EFFECT OF PRICE, SERVICE QUALITY, AND COMPANY IMAGE ON PURCHASE DECISIONS ON JALANJALAN.ID GRESIK - Sutama Wisnu Dyatmika; Lailia Murti Firdaus (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Tour and Travel is one of the most well growth business. This happens in line with the people's lifestyle which emphasizes the balance between life and work. Travel business owners are competing to provide good service to create a good image for the company. The company image exposing the quality of service that is felt by consumers and the price that is in accordance with the expectation of the consumers. The purpose of this research is to determine the effect of price, service quality, and corporate image on purchasing decisions. The population in this study were JalanJalan.id consumers in the period of January to December 2020, namely 240 consumers with a sample of 70 respondents. The sampling technique was carried out by means of quota sampling where this sampling was in accordance with the criteria of the researcher to reach the required quota. The results obtained from the hypothesis test prove that partially the price variable (X1) has a significant effect on purchasing decisions at Jalanjalan.id, the service quality variable (X2) has a significant effect on purchasing decisions on JalanJalan.id, corporate image (X3) has an effect on the decision. purchase on JalanJalan.id, and simultaneously from the price variable, service quality variable, and company image variable have a significant effect on purchasing decisions on JalanJalan.id in Gresik. Keywords: Price, Service Quality, Company Image, Purchase Decision